French literature on screen - Palmer, R. Barton, 1946-; Pettey, Homer B. (Book collections on Project MUSE., 2019)
This collection presents new essays in the complex field of French literary adaptation. Using a variety of textual and interpretive approaches, it sheds light on issues of gender, sexuality, class, politics and social conventions while acknowledging a range of contexts, from the commercial to the archival and the aesthetic. The chapters, written by eminent international scholars, run chronologically from The Count of Monte Cristo through Proust and Bonjour, Tristesse to Philippe Djian's Oh. (adapted for the screen as Elle). Collectively, they fill a need for contemporary discussions on the significance of France's literary representations in the history of global cinema.